Ukuran Perusahaan Memoderasi dampak Profitabilitas dan Intensitas Modal terhadap Penghindaran Pajak - Alun, Jervic Kristian; Louw, Febriana (Ekonomi, Keuangan, Investasi dan Syariah (EKUITAS), 2025)
The purpose of this study is to examine the impact of profitability and capital intensity on tax avoidance, with company size serving as a moderating variable. The population and sample in this study are companies in the Consumer Non-Cyclical sector traded on the Indonesia Stock Exchange with a research period of 2020-2024. This study uses a quantitative approach with secondary data analysis methods from the official website of the IDX, with a purposive sampling technique. The research sample consists of 37 companies for the 2020-2024 period listed on the IDX. The data analysis used is descriptive statistics, classical assumption tests, multiple regression analysis, and moderation regression analysis. The analysis results show that profitability has a negative effect on tax avoidance, while capital intensity has a positive and significant effect on tax avoidance. The MRA test results show that the company size variable does not moderate the effect of profitability and capital intensity on tax avoidance.